Routledge handbook of corruption in Asia - Gong, Ting; Scott, Ian (Routledge handbooks, 2017)
"Corruption in Asia ranges from the venal rent-seeking of local officials to the million-dollar bribes received by corrupt politicians; from excessive position-related consumption to future job offers in the private sector for compliant public servants; from money-laundering to 'white elephant' projects that do little more than line the pockets of developers and their political partners. The Routledge Handbook of Corruption in Asia addresses the theories, issues, and trends in corruption and anticorruption reform that have emerged from this diverse experience"--